TERMITE SPECIES RICHNESS ON THE CAMPUS OF UNIVERSITAS INDONESIA, DEPOK - Primanda, Andya; Ischak, Tubagus M.; Basukriadi, Adi (UI Scholars Hub, 2003)
Termites are a group of invertebrates abundant in forested habitats. In this study, we conduct an inventory and spatial analysis of the termite fauna of the UI campus. The survey records the presence of six termite species (Coptotermes curvignathus, Schedorhinotermes javanicus, Macrotermes gilvus, Microtermes insperatus, Odontotermes grandiceps, and Odontotermes javanicus), most of which had been reported by previous studies. The spatial analysis of termite nest distribution suggests a random scattering of termite nests in the UI campus.